Faktor-Faktor Yang Mempengaruhi Produktivitas Usaha (Studi Kasus Usaha Budidaya Ikan Lele di Kecamatan Batanghari Lampung Timur) - M. Kelvin Setya Wijaya; Sugeng; Jawoto Nusantoro (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the factors that affect the productivity of catfish farming businessin Batanghari District, East Lampung. The main focus of this research is feed quality,environmental management, and seed quality. The method used is a quantitative approachwith data collection through interviews and direct observation at the business site. The resultsof the analysis show that feed quality has a significant positive influence on productivity. Inaddition, good environmental management has also been proven to contribute to increasingcatfish productivity. Seed quality also plays an important role in the success of cultivation.Simultaneously, these three variables have a significant influence on the productivity of thecatfish farming business. The results of this study are expected to provide input for farmersand policy makers to increase catfish cultifation yields sustainably